Delineation of the integrase-attachment and origin-of-transfer regions of the symbiosis island ICEMlSymR7A. - Ramsay, Joshua; Verdonk, Callum J; Sullivan, John T; Williman, Kate M; Nicholson, Leila; Bastholm, Tahlia R; Hynes, Michael F; Ronson, Clive W; Bond, Charles S (2019)
Integrative and conjugative elements (ICEs) are chromosomally-integrated mobile genetic elements that excise from their host chromosome and transfer to other bacteria via conjugation. ICEMlSymR7A is the prototypical member of a large family of "symbiosis ICEs" which confer upon their hosts the ability to form a nitrogen-fixing symbiosis with a variety of legume species. Mesorhizobial symbiosis ICEs carry a common core of mobilisation genes required for integration, excision and conjugative transfer. IntS of ICEMlSymR7A enables recombination between the ICEMlSymR7A attachment site attP and the 3' end of the phe-tRNA gene. Here we identified putative IntS attP arm (P) sites within the attP region and demonstrated that the outermost P1 and P5 sites demarcated the minimal region for efficient IntS-mediated integration. We also identified the ICEMlSymR7A origin-of-transfer (oriT) site directly upstream of the relaxase-gene rlxS. The ICEMlSymR7A conjugation system mobilised a plasmid carrying the cloned oriT to Escherichia coli in an rlxS-dependent manner. Surprisingly, an in-frame, markerless deletion mutation in the ICEMlSymR7A recombination directionality factor (excisionase) gene rdfS, but not a mutation in intS, abolished mobilisation, suggesting the rdfS deletion tentatively has downstream effects on conjugation or its regulation. In summary, this work defines two critical cis-acting regions required for excision and transfer of ICEMlSymR7A and related ICEs.